Analisis Kemampuan Mahasiswa pada Tugas Proyek Pemodelan Persamaan Diferensial Parsial - Arjudin Arjudin; Sripatmi Sripatmi; Ketut Sarjana; Nani Kurniati (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
The purpose of this study is to describe the characteristics of students' abilities in completing Partial Differential Equation (PDP) modeling project. This is motivated by the problem of students' difficulties in solving PDP applied problems, where the questions refer to modeling project assignments. This study is considered important because previous studies have examined more individual abilities, while projects have a broader scope, including the ability to solve problems by interaction. PDP Modeling Project are divided into four stages, namely: (1) Problem Context, (2) PDP Modeling, (3) PDP Model Completion, and (4) Example and solutions. This type of research is descriptive qualitative, conducted on students of the Mathematics Education, FKIP, University of Mataram. The instruments are project assignments and presentation assessment sheets. The results showed that the results of the project assignments were grouped into 3 categories, namely Unstructured (TT) which gave rise to inappropriate mathematical models because they were still in the form of ordinary differential equations instead of partial differential equations, the most dominant being 40% Incompletely Structured (T-TL) which gave rise to partial differential equation models but were inappropriate in applying them to case examples, and Completely Structured (T-L) which were able to carry out the project stages which included the problem context, PDP modeling, model completion, and solving the case correctly. The results of the PDP modeling project categorization can be mapped to the level of understanding that describes the characteristics of students who make scientific contributions leading to differentiated learning strategies and TaRL.